Remembering the memorial of Jean-Francois Lyotard - W. McClure (Law Text Culture, 1998)
Recently [early May] I attended the I.A.:P.L. 'Interrogating the Image' conference at the University of California, Irvine. During the conference, a last minnte decision was made to hold a memorial for Jean-Fran ois Lyotard. Lyotard died on the 21st of April. Amongst those who spoke at the memorial were, Jacques Derrida, David Carroll, Mary Lydon, Hugh Silverman and Andrew Benjamin.